The evolution of a security community through a process of integration: problems and prospects for the SADC region - Šebek, Vita (Rhodes University, Faculty of Humanities, Department of Political Studies, 2002)
This thesis examines the security problematic of African states and focuses more particularly on the SADC region. It links the security problematic with the transactionalist approach to (supra)national integration and the concept of a security community, introduced into internatIonal relations theory by Karl Deutsch and his colleagues. In relation to the (in)security of SADC member states, the thesis attempts to demonstrate that national integration of these states (i.e. the establishment of an amalgamated security community) has at least to accompany if not precede the establishment of a security community at the regional level (i.e. a pluralistic security community). Since threats to the security of SADC member states are mainly nonmilitary in nature, the 'realist' concept of security is broadened to include political, economic, societal and environmental aspects of security at different levels. Furthermore, Deutsch's concept of a security community is redefined in line with the 'new security thinking' and adapted to the situation in African states. Moreover, this thesis attempts to demonstrate that it is essential for SADC member states to become strong and socio-economically cohesive in order to improve their competitiveness in relation to developed states, especially in their ability to deal with internal and ransnational/regional threats to their security, which are (in)directly caused and perpetuated by the lack of national integration, inefficient state-making and underdevelopment - the sources of their weakness.
Keywords: Political stability -- Africa, Southern; Southern African Development Community; National security -- Africa, Southern; Africa, Southern -- Economic integration